Balancing a multistage vehicle number plate production line using effective cycle time model - Nwanya, Stephen C.; Achebe, Celestine N. (Universitas Serang Raya, 2020)
Shortest product cycle time is a key criterion for job sequencing and measuring competitiveness among entrepreneurial-based firms. Now, the long waiting time of job orders constitutes a deterministic production line problem in vehicle number plate production plants in Nigeria. Case studies were conducted on those plants, confidentially identified in this paper as A, B, C, and D. Delays caused by non-value-adding work processes are major culprits among other contributors to the long queues at these plants. The value stream mapping technique was applied to identify non-value adding activities before the production line was balanced using an effective cycle time model. The index cases to a balanced line, as shown in the results, are increases in process rate by 41 %, 59 %, 42 %, and 71 % for A, B, C, and D, respectively, and overall line efficiency. Next, the system capacities correspondingly increased with the elimination of wastages. These increments imply that bottleneck activities have been minimized, and we have a balanced production line. The devised solution procedure is reliable and recommended to other line manufacturing concerns that experience delays and bottleneck problems.